Assessment of elasticity of colorectal cancer tissue, clinical utility, pathological and phenotypical relevance. Issue 9 (20th August 2015) - Kawano, Shingo; Kojima, Motohiro; Higuchi, Yoichi; Sugimoto, Motokazu; Ikeda, Koji; Sakuyama, Naoki; Takahashi, Shinichiro; Hayashi, Ryuichi; Ochiai, Atsushi; Saito, Norio
<x xml:space="preserve">Abstract</x> Generally, cancer tissue is palpated as a hard mass. However, the elastic nature of cancer tissue is not well understood. The aim of the present study was to evaluate the clinical utility of measuring the elastic modulus (EM) in colorectal cancer tissue. Using a tactile sensor, we measured the EM of 106 surgically resected colorectal cancer tissues. Data on the EM were compared with clinicopathological findings, including stromal features represented by Azan staining and the α‐SMA positive area ratio of the tumor area. Finally, a cDNA microarray profile of the tumors with high EM were compared with the findings of tumors with low EM. A higher EM in tumors was associated with pathological T, N, and M‐stage tumors (P < 0.001, P = 0.001 and P = 0.011, respectively). Patients with high EM tumors had shorter disease‐free survival than had patients with low EM. The EM showed strongly positive correlation with the Azan staining positive area ratio (r = 0.908) and the α‐SMA positive area ratio (r = 0.921). Finally, the cDNA microarray data of the tumors with high EM revealed a distinct gene expression profile compared with data from those tumors with low EM. The assessment of the elasticity of colorectal cancer tissue may allow a more accurate clinical stage and prognosis estimation. The distinct phenotypical features of the high EM tumors and their strong association with stromal features suggest the existence of a biological mechanism involved in this phenomenon that may contribute to future therapy.